Sex, Court Records, and Labour History - Maynard, Steven (Labour / Le Travail, 1994)
Examines crown attorney prosecution files at the Archives of Ontario as primary source material on communism in Canada, union organizing, strike activity, state surveillance, the role of women and youth in left-wing politics and the labour movement, and gender and sexual relations in labour organizing. Discusses several court cases and reproduces a 1929 Communist Party leaflet used as evidence in charging four women with circulating seditious pamphlets. Concludes that the evidence in the files sheds light on the collective struggle for economic and social justice for working people.
Keywords: COMMUNIST parties; Canada; Communists; Court records; Labor movement; Political activity; STRIKES & lockouts -- History; WOMEN communists